ANALYSIS OF IMPOLITENESS COMMENTS OF NETIZEN ON NAJWA SHIHAB YOUTUBE CHANNEL - Sinaga, Askima Rohmauli; Saragi, Christina Natalina; Silitonga, Harpen (Dharmas Education Journal (DE_Journal), 2024)
This study is entitled "Analysis of Impoliteness Comments of Netizens on Najwa Shihab YouTube Channel". This study aims to examine the types of impoliteness strategies used by netizens in speaking in the comments column of Najwa Shihab's YouTube channel on the show "Ganjar Pranowo Bicara Gagasan" based on Jonathan Culpeper’s theory. In this study, the research design used is a qualitative descriptive method to analyze the types of impoliteness strategies used by netizens in commenting on the comment section of Najwa Shihab's YouTube channel on the "Ganjar Pranowo Bicara Gagasan" video uploaded in September 2023. Data will be obtained from transcripts of printed materials related to incivility, with Culpeper's theory as the basis of analysis. The results of this study identified four types of impoliteness strategies from 100 comments studied contain impoliteness strategies on the video, the four categories of impoliteness identified include: Bald on Record Impoliteness (25%), Positive Impoliteness (22%) with Insukting Others (3%), Rejecting Similarities with the Listener (1%), Diverting Topics that are Sensitive or do not want to be Discussed (5%), Using Inappropriate Code (1%), Not Interested in Conversation (6%), Look For Differences Opinion (4%), and Using Unclear and Confidential Language (2%), negative impoliteness (26%), and Sarcasm or Mock impoliteness (27%), while Withhold Politeness is not found because it can only be found in oral speech. Based on the analysis, Sarcasm or Mock Impoliteness (27%) is the most dominant type of impoliteness strategy. From these findings, it can be concluded that Indonesian netizens often express meanings that are opposite to the words they actually say, which aims to criticize or make fun of their interlocutors in a subtle way.